Can Phishing Tank Survey Response Rates? Evidence from a Natural Experiment. Issue 4 (November 2019) - Brenner, Philip S.
In today's survey climate, many individuals doubt the legitimacy of survey invitations. Phishing, an Internet-based fraud that tricks users into disclosing private information, has the potential to further erode the perceived legitimacy of e-mailed survey invitations and harm cooperation. However, no study has tested the effect of phishing on response rates. This article reports on a natural experiment examining phishing's effect on survey response. University faculty and staff received an invitation to participate in an annual web survey on satisfaction with information technology (IT) services followed by a request to participate in a second "survey" ostensibly sent by another university department. However, the second survey invitation was a simulated phishing attack sent by the IT department. Analysis of response rates and the timing of responses from each of the last five years of the legitimate survey suggests that the phishing simulation dramatically reduced response compared to predictions based on previous years.